Location Privacy Leakage through Sensory Data. (6th August 2017) - Liang, Yi; Cai, Zhipeng; Han, Qilong; Li, Yingshu
Abstract : Mobile devices bring benefits as well as the risk of exposing users' location information, as some embedded sensors can be accessed without users' permission and awareness. In this paper, we show that, only by using the data collected from the embedded sensors in mobile devices instead of GPS data, we can infer a user's location information with high accuracy. Three issues are addressed which are route identification, user localization in a specific route, and user localization in a bounded area. The Dynamic Time Warping based technique is designed and we develop a Hidden Markov Model to solve the localization problem. Real experiments are performed to evaluate our proposed methods.